2019
DOI: 10.1101/761452
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Complex genetic admixture histories reconstructed with Approximate Bayesian Computations

Abstract: Admixture is a fundamental evolutionary process that has influenced genetic patterns in numerous species. Maximum-likelihood approaches based on allele frequencies and linkage-disequilibrium have been extensively used to infer admixture processes from dense genome-wide datasets mostly in human populations. Nevertheless, complex admixture histories, beyond one or two pulses of admixture, remain methodologically challenging to reconstruct, especially when large datasets are unavailable. We develop an Approximate… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 78 publications
(121 reference statements)
0
4
0
Order By: Relevance
“…They can be utilized as input for downstream operations such as forward steps of a specific evolutionary process for which they can become variations of the real datasets (similar to bootstrap), or they can be the sole input when the real dataset is not accessible. Initializing a simulation with real data is a procedure that is commonly used in population genetics [48,49]. Our results showed that GAN AGs are possibly underfitting while, on the contrary, RBM AGs are overfitting, based on distribution of minimum distance to the closest neighbour (S8 Fig) and AA TS scores (S13A Fig), although we showed how overfitting could be restrained by integrating AA TS scores within our models as a criterion for early stopping in training (before the networks start overfitting) and by modifying the RBM sampling scheme.…”
Section: Discussionmentioning
confidence: 99%
“…They can be utilized as input for downstream operations such as forward steps of a specific evolutionary process for which they can become variations of the real datasets (similar to bootstrap), or they can be the sole input when the real dataset is not accessible. Initializing a simulation with real data is a procedure that is commonly used in population genetics [48,49]. Our results showed that GAN AGs are possibly underfitting while, on the contrary, RBM AGs are overfitting, based on distribution of minimum distance to the closest neighbour (S8 Fig) and AA TS scores (S13A Fig), although we showed how overfitting could be restrained by integrating AA TS scores within our models as a criterion for early stopping in training (before the networks start overfitting) and by modifying the RBM sampling scheme.…”
Section: Discussionmentioning
confidence: 99%
“…Several population genetics methods have been developed during the past 10 years to infer, from genomic data only, how many recurring or more temporary events of admixture, and their associated timings and respective intensities, have shaped the observed genetic patterns in admixed populations today (41)(42)(43).…”
Section: Reconstructing the Admixture Histories Of Enslaved-african D...mentioning
confidence: 99%
“…Admixture-gene flow between previously diverged populations to form a new population with ancestry from both source populations-provides a particularly rapid opportunity for selection to act in a population by introducing alleles previously adapted in a source population into the admixed population (Huerta-Sánchez et al, 2014;Jeong et al, 2014;Norris et al, 2020;Racimo et al, 2015). Additionally, in recent human admixture, ancestry contributions from each source population are often large enough to introduce alleles at intermediate frequencies, potentially avoiding loss from drift (V. Fernandes et al, 2019;Fortes-Lima et al, 2019;Mathias et al, 2016;Ruiz-Linares et al, 2014). More generally, admixture is ubiquitous in human history (G. B.…”
Section: Introductionmentioning
confidence: 99%